2019
DOI: 10.3390/ijms20061444
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the High-Affinity Drug Ligand Binding Site of Mouse Recombinant TSPO

Abstract: The optimization of translocator protein (TSPO) ligands for Positron Emission Tomography as well as for the modulation of neurosteroids is a critical necessity for the development of TSPO-based diagnostics and therapeutics of neuropsychiatrics and neurodegenerative disorders. Structural hints on the interaction site and ligand binding mechanism are essential for the development of efficient TSPO ligands. Recently published atomic structures of recombinant mammalian and bacterial TSPO1, bound with either the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…The drug and cholesterol binding domains were found to be in distinct domains of the protein results confirmed by NMR [87,88,90]. Moreover, these findings were further confirmed in structural studies by NMR and crystallography studies that reported the atomic structure of TSPO [91][92][93][94][95][96]. These studies also proposed that the functional TSPO is a dimer, that ligand binding to TSPO can promote cholesterol movement, and that cholesterol is an allosteric regulator of TSPO [91,93,94,97].…”
Section: Molecular Structure and Cellular Functionsmentioning
confidence: 52%
“…The drug and cholesterol binding domains were found to be in distinct domains of the protein results confirmed by NMR [87,88,90]. Moreover, these findings were further confirmed in structural studies by NMR and crystallography studies that reported the atomic structure of TSPO [91][92][93][94][95][96]. These studies also proposed that the functional TSPO is a dimer, that ligand binding to TSPO can promote cholesterol movement, and that cholesterol is an allosteric regulator of TSPO [91,93,94,97].…”
Section: Molecular Structure and Cellular Functionsmentioning
confidence: 52%
“…The spontaneous change that we observe in the orientation of the F100 side chain may indicate that it is involved in placing the ligand inside the binding pocket, but not crucial for its binding, and that this role is left to F99 and Y34, as suggested by [58]. Deeper studies will of course need to be done to explore in detail the exact role of these three residues.…”
Section: Pk11195 Interactions With the Htspo Modelmentioning
confidence: 82%
“…(iii) The W95XPXF99 motif is fully conserved among human, mouse, and Rs TSPO, while the Bc TSPO sequence differs significantly in this region ( Figure 1 , blue rectangle). This motif is conserved also in other prokaryotic and eukaryotic TSPO sequences [ 40 , 57 ], and it was suggested to play a role in oligomerization processes [ 49 ], as well as in ligand binding [ 34 , 58 ]. In the Mo TSPO experimental structure, W95 points into the binding cavity and F99 is oriented toward the membrane, whereas in the Rs TSPO structure, both residues point into the binding pocket.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Drug-protein interactions can be observed as spectral changes in the far-UV region rather than in the near-UV region because they are frequently accompanied by changes in protein secondary structures. [18][19][20][21][22] However, not only proteins and drug substances but also solvents generally show light absorption in the far-UV region. Such light absorption imposes limits on the concentrations of target proteins and drug substances for CD spectroscopy, which can make it difficult to detect changes in the CD spectra originating from drug-protein interactions.…”
Section: Circular Dichroism and Absorption Spectroscopymentioning
confidence: 99%
“…CD spectroscopy is used for observing structural changes of proteins and nucleic acids upon ligand binding. [18][19][20][21][22] DSC is used for observing the binding of ligands to proteins as an increase in melting temperature of the proteins, [22][23][24][25][26] while ITC is used for directly measuring the heat that is associated with ligand binding. 22,27 In addition, the solubilization capacities of DMSO, ACN, and dioxane for poorly soluble compounds were examined to evaluate their potential for practical use in drug-protein interaction analyses.…”
Section: Introductionmentioning
confidence: 99%